2020
DOI: 10.1103/physrevb.101.125110
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of dipoles and spins in κ(BEDTTTF)2X , where X=Hg(

Abstract: We combine first-principles density functional calculations with empirical relationships for the Coulomb interactions in the monomer model of κ-(BEDT-TTF) 2 X. This enables us to calculate the parameters for the model of coupled dipolar and spin degrees of freedom proposed by Hotta [Phys. Rev. B 82, 241104 (2010)], and Naka and Ishihara [J. Phys. Soc. Jpn. 79, 063707 (2010)]. In all materials studied, retaining only the largest interactions leads to a transverse-field Ising model of the dipoles. This quantifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…At the same time, the local moments grow as characterized by a Curie-Weiss (C-W) temperature, ∼25 K [the inset of Fig. 3(c)], which is consistent with the first-principles calculations that project an exchange interaction of ∼ 10 2 K between spins on ET molecules [31] or ET dimers [35]. Thus, in the temperature range of 20-50 K, the spin clusters gradually take shape with middle-scale staggered spin configurations developed.…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, the local moments grow as characterized by a Curie-Weiss (C-W) temperature, ∼25 K [the inset of Fig. 3(c)], which is consistent with the first-principles calculations that project an exchange interaction of ∼ 10 2 K between spins on ET molecules [31] or ET dimers [35]. Thus, in the temperature range of 20-50 K, the spin clusters gradually take shape with middle-scale staggered spin configurations developed.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, we succeeded in detecting the charge anomaly in κ-(ET) 2 Cu 2 (CN) 3 by 63,65 Cu-NQR experiments [10]. This technique will greatly contribute to elucidating the physical properties of systems in which the charge degree of freedom is important, e.g., β -(ET) 4 [(H 3 O)Ga(C 2 O 4 ) 3 ] • C 6 H 5 NO 2 [47,48] and κ-(ET) 2 Hg(SCN) 2 Y (Y = Cl, Br) [5][6][7][8], where 69,71 Ga, 35,37 Cl, and 79,81 Br NMR experiments will be appropriate probes.…”
Section: Fluctuation At Temperatures Immediately Above T Cmentioning
confidence: 99%
“…Accordingly, electronic spin plays a major role in the dimer-Mott system; however, physical properties originating from the charge degree of freedom have also been recently observed. For example, dielectric anomalies in many types of κ-type organic insulators [2][3][4], charge ordering and a quantum dipole liquid in κ-(ET) 2 Hg(SCN) 2 Y (Y = Cl, Br) [5][6][7][8], and a mysterious physical property called the 6 K anomaly in the quantum-spin-liquid candidate κ-(ET) 2 Cu 2 (CN) 3 [9,10], have been reported. These phenomena have attracted considerable attention from the perspective of multiferroicity.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing J , the spins completely tilt towards a common plane, leading to the coplanar spin-vortex crystal (SVC) [7,11]. κ-Mn differs from other organics primarily in terms of J /J ≈ (t /t) 2 , which can been estimated as ∼ 0.2−0.35 for κ-Cl [48,[52][53][54], ∼ 0.8 − 1.2 for κ-Cu [48,52,53,55], and ∼ 2 for κ-Mn. Recent DMRG studies [17,19] of the Hubbard model have found a similar phase diagram, enriched by QSL states.…”
mentioning
confidence: 99%